Serapan Fosfat dan Respon Fisiologis Tanaman Cabai Merah Cultivar Hot Beauty Terhadap Mikoriza dan Pupuk Fosfat PadaTanah Ultisol - Siti Zulaikha; Gunawan Gunawan (Bioscientiae, 2006)
The research aimed to study the influence of interaction between inoculation of  mycorhiza and the dose of phosphate fertilizer to phosphate nutrient absorption and physiological response of red chili on Ultisol soil. Using Randomized Block Design, the two factor factorial trial was conducted in three replications. The first factor was four levels of  mycorhiyza, i.e., 0, 3, 5, and 7 of  mycorhiza tablets, and the second factor was the levels of fertilizer dose, i.e., 90, 135, and 180 kg of  P2O5 ha-1. The seeds of 21 days old were planted in the ultisol soils placed on the polybags. The observed parameters were phosphatte nutrient absorption, crop growth rate (CGR), relative growth rate (RGR), and net assimilation rate (NAR). The result revealed that combination treatment between 7 tablets per plant of mycorhiza inoculation and phosphate dose of 135 kg ha-1 resulting the highest plant growth rate on 4 – 5 weeks after planting (wap), net assimilation rate on 3 – 5 wap, and  phosphate nutrient absorption (6,86 mg g-1).